Evolution of childhood : relationships, emotion, mind - Konner, Melvin (Belknap Press of Harvard University Press, 2011)
Takes a comprehensive Darwinian interpretation of human development. Looking at the entire range of human evolutionary history, Konner tells the story of how cross-cultural and universal characteristics of our growth from infancy to adolescence became rooted in genetically inherited characteristics of the human brain--From publisher description.